Pracoholizm w kategoriach deprecjacji pracy pielęgniarki. Wybrane aspekty = Workaholism in categories of nurses' work depreciation. Chosen aspects - Ewa Stychno; Kinga Kulczycka (Kazimierz Wielki University, 2016)
Stychno Ewa, Kulczycka Kinga. Pracoholizm w kategoriach deprecjacji pracy pielęgniarki. Wybrane aspekty = Workaholism in categories of nurses' work depreciation. Chosen aspects. Journal of Education, Health and Sport. 2016;6(10):11-21. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.159507 http://ojs.ukw.edu.pl/index.php/johs/article/view/3920       The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.09.2016. Revised 24.09.2016. Accepted: 07.10.2016.       Pracoholizm w kategoriach deprecjacji pracy pielęgniarki. Wybrane aspekty Workaholism in categories of nurses' work depreciation. Chosen aspects   Stychno Ewa, Kulczycka Kinga   Katedra i Zakład Zarządzania w Pielęgniarstwie, Wydział Nauk o Zdrowiu UM w Lublinie Chair and Department of Management in Nursing Faculty Health Sciences Medical University of Lublin       Słowa kluczowe: pielęgniarki, pracoholizm, stres, wypalenie zawodowe Keys words: nurses, workaholism, stress, occupational burnout syndrome       Streszczenie Pracoholizm jest zjawiskiem badanym przede wszystkim przez psychologów, którzy koncentrują się na relacjach pracoholika z bliskimi mu osobami. Ale skutki tego uzależnienia ujawniają się także w funkcjonowaniu pielęgniarki w środowisku pracy. Pielęgniarstwo należy do zawodów, w których ciągły stres jest nieodłącznym aspektem, wynikającym z natury pracy. Niewłaściwe radzenie sobie ze stresem w sytuacjach trudnych prowadzi do powstania zespołu wypalenia zawodowego. Dlatego zagadnienie to powinno stanowić obszar poszukiwań badawczych także dla kadry zarządzającej kapitałem ludzkim. Cel pracy Celem niniejszego opracowania jest omówienie pracoholizmu i jego negatywnych skutków (stres i wypalenie zawodowe) w kategoriach deprecjacji pracy pielęgniarki. Pracoholizm zaburza równowagę pomiędzy pracą zawodową a życiem prywatnym. Ograniczeniu ulega zaangażowanie pracownika w życie rodzinne, brakuje czasu na realizację własnych zainteresowań. Sytuacja taka powoduje stres i zjawisko wypalenia zawodowego, a w także negatywne konsekwencje dla jednostki, jak i jej najbliższego otoczenia. Narastające trudności związane z wykonywaną pracą, stała rywalizacja, niepewność zatrudnienia będą potęgowały negatywny aspekt pracoholizmu i osłabiały mechanizmy przystosowawcze.  Wnioski Konieczne jest uświadomienie sobie przez kadrę zarządzającą faktu, iż pracownicy - pracoholicy nie przynoszą organizacji tylu korzyści, co pracownicy posiadający umiejętność panowania nad własnym życiem, pracą i rodziną.   Summary Workaholism is a phenomenon researched mostly by psychologists, whom focalize on the workaholic's relations with his relatives. Nursing is one professions in which stress is irreplaceable and is a result of the nature of the profession itself. Inappropriate dealing with stress leads to developing the burnout syndrome. Yet this addiction has a negative influence on workaholic's actions in his work environment. Therefore this issue should be taken into an area of scientific research also by staff managers of human resources. Aim of study This study's purpose is to research workaholism and its negative impact in categories of nurses' work depreciation.        Workaholism disrupts the balance between professional work and personal life. The addict's commitment to his family becomes severely limited, he lacks time for personal arrangements and interests. Such state of affairs causes further stress and burnout, which spreads over the individual's relatives. Increasing difficulties related to performed work, constant state of competition, uncertainty of employment will be intensifying  the negative aspect of  workaholism and weakening adaptive mechanisms. Conclusion Therefore, it is vital for the management staff to realise that employees-workaholics do not benefit the company as much as employees with the ability to control their own lives, work and family.